Impact of Monitoring Requests on Publics’ Assignment of Blame and Praise towards ADS Level 3 Vehicles - Liam Kettle; Madeleine M. McCarty; Kassidy L. Simpson; Yi-Ching Lee (Human Behavior and Emerging Technologies)
As vehicle automation capabilities increase, driving control shifts from the human to the vehicle system. However, concerns arise regarding responsibility following critical events and the publics’ trust and acceptance of vehicles equipped with automated driving systems (ADS). The current study examined how participants assigned blame and praise to ADS-equipped vehicles and human drivers following collisions or near-misses and how these attributions were impacted by a virtual driving assistant that administered monitoring requests. Based on literature, our primary hypothesis was that more blame would be assigned to the human and more praise assigned to the ADS when the driving assistant was present. Additionally, we hypothesized greater reported trust towards ADS-equipped vehicles when the driving assistant was present. Participants read vignettes of automated driving, watched corresponding videos, and then self-reported trust, acceptance, anthropomorphism, and assignment of blame and praise. All hypotheses were supported indicating that significant effects were observed: participants assigned greater blame to the human when asked to actively monitor the driving environment and assigned greater praise to the ADS when it alerted the human driver. Additionally, participants reported greater trust and anthropomorphism of the ADS when the driving assistant was present. These findings suggest that explicitly communicating monitoring responsibility through a driving assistant significantly impacts the publics’ opinion of responsibility following critical events. These findings provide initial support for a solution to improve driver safety as well as policy implications regarding positive perceptions and the adoption of ADS-equipped vehicles.